Dansko Announces New President: Founder Mandy Cabot to continue as CEO and Board Chair, Jim Fox named President (PR Newswire, 2015)
"Taking a step back will allow me more time to focus on being the company visionary I originally set out to be and continue to propel our passion for uncommon comfort with unexpected style," said Cabot. Since joining Dansko as CFO in 2006, Fox created and implemented financial and operational controls that have served as the foundation for profitable, well-managed growth.